2014
DOI: 10.1016/j.ijsolstr.2014.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size distribution on micro- and macromechanical response of granular packings under compression

Abstract: Please cite this article as: Wiącek, J., Molenda, M., Effect of particle size distribution on micro-and macromechanical response of granular packings under compression, International Journal of Solids and Structures (2014), doi: http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 23 publications
3
29
1
1
Order By: Relevance
“…We observe that the bulk modulus decreases with polydispersity and the inter-particle frictions considered. This result is in agreement with those obtained in compressional three-dimensional granular packings [16,17,21], where denser packings are achieved since contact deformations and grains rearrangements occur during compression. Furthermore, Fig.2 shows that the mean coordination number decreases, while porosity reaches a maximum, for δ = 40%, to then decrease weakly as polydispersity and particle friction grow.…”
Section: Effect Of Polydispersity On Bulk Modulussupporting
confidence: 91%
See 2 more Smart Citations
“…We observe that the bulk modulus decreases with polydispersity and the inter-particle frictions considered. This result is in agreement with those obtained in compressional three-dimensional granular packings [16,17,21], where denser packings are achieved since contact deformations and grains rearrangements occur during compression. Furthermore, Fig.2 shows that the mean coordination number decreases, while porosity reaches a maximum, for δ = 40%, to then decrease weakly as polydispersity and particle friction grow.…”
Section: Effect Of Polydispersity On Bulk Modulussupporting
confidence: 91%
“…Results reported previously, have shown that increasing polydispersity of a compacted granular system reduces slightly the bulk modulus [17,21]. A preliminary work [27] showed experimentally that the strongest force chains emerge at peak effective stiffness, evidencing a latent relation between both.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Energy dissipated in the collisions was proportional to the mass of the colliding bodies, resulting in greater energy dissipation in systems composed of larger granules. DEM simulations of uniaxial compression of polydisperse sphere packings, conducted by Wiącek and Molenda [19], have shown that a loss energy increased as the degree of particle size heterogeneity increased. It is well known that efficiency of industrial processes involving handling of granular materials significantly depends on dissipation of energy in system.…”
Section: Introductionmentioning
confidence: 99%
“…In additional studies, Martin et al [113] analyzed particle rearrangement during powder compaction, and Wiacek and Molenda [114] investigated the effects of the particle size distributions on the response under compression.…”
Section: Die Filling and Tablet Compactionmentioning
confidence: 99%